125 Years of Aspirin: Status of Analytical Methods - dos Santos Galvão, Natália Sabina; Sinzervinch, Aline; Lustosa, Isadora Alves; Kogawa, Ana Carolina (Current Pharmaceutical Design, 2025)
Aspirin, an analgesic, antipyretic and non-steroidal anti-inflammatory drug, was a fascinating discovery that became the precursor to one of the oldest pharmaceutical success stories. It was discovered in 1899 by Felix Hoffman and patented in 1900. In 2024, Aspirin turns 125 years old and is still one of the best-selling medicines today. This review aims to celebrate 125 years of Aspirin and show the status of analytical methods available in the literature to evaluate pharmaceutical products based on Acetylsalicylic Acid (ASA). In addition, it contextualizes them with the current needs of green and clean analytical chemistry. ASA, despite being consolidated in the consumer market, embraces continuous improvement as it is a fundamental part of studies for other new purposes and studies with associations with other active ingredients. In the manuscripts available in the literature, ASA is predominantly evaluated by HPLC (41%) and UV-vis (41%) methods, which use methanol (21.82%) and acetonitrile (18.18%), followed by buffer (16.36%). The most evaluated pharmaceutical matrix is ASA tablets (40%), followed by ASA tablets in combination with other drugs (26%). While ASA continues to innovate in the market through new forms of delivery and combinations, as well as intended purposes, the analytical methods for evaluating its pharmaceutical products do not. They continue with non-eco-efficient analytical options, which can significantly improve and meet the current demand for green and sustainable analytical chemistry.
Keywords: aspirin